TRANSDISCIPLINARY INNOVATION IN IRRIGATED SMALLHOLDER AGRICULTURE IN AFRICA. (30th January 2020) - Froebrich, Jochen; Ludi, Eva; Bouarfa, Sami; Rollin, Dominique; Jovanovic, Nebo; Roble, Maria; Ajmi, Tarek; Albasha, Rami; Bah, Sékou; Bahri, Haithem; Barberá, Gonzalo; van Beek, Christy; et al.
Abstract: Boosting the productivity of smallholder farming systems continues to be a major need in Africa. Challenges relating to how to improve irrigation are multi‐factor and multisectoral, and they involve a broad range of actors who must interact to reach decisions collectively. We provide a systematic reflection on findings from the research project EAU4Food, which adopted a transdisciplinary approach to irrigation for food security research in five case studies in Ethiopia, Mali, Mozambique, South Africa and Tunisia. The EAU4Food experiences emphasize that actual innovation at irrigated smallholder farm level remains limited without sufficient improvement of the enabling environment and taking note of the wider political economy environment. Most project partners felt at the end of the project that the transdisciplinary approach has indeed enriched the research process by providing different and multiple insights from actors outside the academic field. Local capacity to facilitate transdisciplinary research and engagement with practitioners was developed and could support the continuation and scaling up of the approach. Future projects may benefit from a longer time frame to allow for deeper exchange of lessons learned among different stakeholders and a dedicated effort to analyse possible improvements of the enabling environment from the beginning of the research process. © 2020 The Authors. Irrigation and Drainage published by John Wiley & Sons Ltd on behalf of International Commission for Irrigation and Drainage Résumé: Le renforcement de la productivité des petites exploitations agricoles demeure une nécessité majeure en Afrique. Les problèmes relatifs à la façon d'améliorer l'irrigation sont multifactoriels et multisectoriels, impliquant un large éventail d'acteurs qui doivent interagir pour prendre des décisions collectives. Le projet de recherche EAU4Food a adopté une approche transdisciplinaire et participative dans cinq situations en Afrique du Sud, en Éthiopie, au Mali, au Mozambique et en Tunisie. Ces expériences montrent que l'innovation au niveau des exploitations agricoles ne peut se faire sans prendre en compte leur environnement et le cadre plus général des politiques agricoles. La plupart des partenaires du projet estiment que l'approche transdisciplinaire a effectivement enrichi le processus de recherche en diversifiant les points de vue. Les capacités locales de recherche transdisciplinaire ont été renforcées et cela permettra la poursuite et l'extension de cette approche. Il serait intéressant, pour les futurs projets, de disposer de plus de temps pour avoir des échanges d'expérience plus longs entre les différentes parties‐prenantes, et de prendre en compte dès le départ l'environnement des exploitations pour y faciliter l'innovation. © 2020 The Authors. Irrigation and Drainage published by John Wiley & Sons Ltd on behalf of International Commission for Irrigation and Drainage